Correction: Epidemiology, Microbiology and Mortality Associated with Community-Acquired Bacteremia in Northeast Thailand: A Multicenter Surveillance Study. - Kanoksil, M; Jatapai, A; Peacock, S; Limmathurotsakul, D (2013)
[This corrects the article on p. e54714 in vol. 8.].